Working with autistic people in the criminal justice and forensic mental health systems: a handbook for practitioners - Tyler, Nichola; Sheeran, Anne (Issues in forensic psychology, 2022)
"Working with Autistic People in the Criminal Justice and Forensic Mental Health System: A Handbook for Practitioners is the first book to focus specifically on the best practice for working with autistic people in criminal justice and forensic mental health settings. Integrating current theory, research, and clinical practice, this book provides a practical guide for multidisciplinary practitioners working with autistic people who have offended, at all stages in their pathway, regardless of the nature of offending"--